Burkitt'S lymphoma in pregnancy with bilateral breast involvement: Case report with review of the literature - Savvari, P.; Matsouka, C.; Barbaroussi, D.; Christoulas, D.; Nikitas, N.; Dimopoulos, M.-A.; Papadimitriou, C.A. (Onkologie, 2010)
Background: Burkitt's lymphoma (BL) in pregnancy presenting with breast involvement is a rare clinical entity, and only 13 cases have been reported so far. Case Report: We describe the case of a 28-year-old postpartum woman who presented with markedly enlarged breasts caused by BL. She was treated with 8 cycles of the CALGB 10002 regimen, as well as with irradiation to both breasts. After achieving a complete objective response, the patient received consolidation with high dose BEAM followed by autologous stem cell transplantation. 20 months after the initial diagnosis, our patient remains alive and relapse-free. Data extracted from the published case reports include information regarding demographic details, type of treatment, sites of disease, and survival. The clinical outcome of the reviewed cases was very unfavorable. Conclusions: BL affecting breasts during pregnancy or lactation is a rare entity that requires a prompt diagnosis and an aggressive therapeutic approach. © 2010 S. Karger AG, Basel.
Keywords: Breast; Burkitt's lymphoma; Pregnancy